A low-rank coal-based two-dimensional porous nanosheet, preparation method and application
Through the preparation method of low-order coal-based two-dimensional porous nanosheets, the problems of complex preparation process, high cost and low yield in the prior art are solved, and efficient and low-cost nanosheet preparation is achieved, and electrochemical performance is improved.
Patent Information
- Application Number
- CN202411372057.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The existing porous carbon nanosheet preparation process is complex, high cost and low yield, which limits the development of hybrid capacitors.
Low-order coal-based two-dimensional porous nanosheets are prepared by purification, mixing with surfactant and alkali, drying, high-temperature carbonization treatment and pickling.
It realizes high yield and low cost two-dimensional porous nanosheet preparation, improves the utilization efficiency of electrode materials in electrochemical reactions, and is suitable for cathode materials of high-performance hybrid capacitors.
Smart Images

Figure CN118888350B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy storage technology, and specifically to a low-rank coal-based two-dimensional porous nanosheet, a preparation method and an application thereof. Background Art
[0002] With the advent of the electric age, modern society's requirements for energy storage devices are developing towards high energy density, high power density, high safety and long cycle life. Hybrid capacitors (Sodium Ion Capacitor, SIC) are expected to achieve a leapfrog improvement in the comprehensive performance of electrochemical energy storage devices, such as high energy, high power, long life and low cost, because they have the characteristics of high energy of batteries and high power of supercapacitors. The negative terminal of the hybrid capacitor is a "battery-type" electrode that undergoes a Faraday reaction, including various carbon materials, titanium-based materials and conversion materials, while the positive terminal is a "capacitor-type" electrode that undergoes an adsorption reaction, mainly porous carbon materials. Based on this special structure, hybrid capacitors effectively combine the advantages of batteries and supercapacitors. However, different energy storage mechanisms cause a great imbalance in the capacity matching of the positive and negative electrodes; the energy storage mechanism of the negative electrode material is a Faraday reaction, with a high specific capacity, while the specific capacity of the porous carbon positive electrode material based on the physical adsorption energy storage mechanism is low. Therefore, the low-capacity positive electrode material seriously restricts the development of hybrid capacitors. Based on this, developing positive electrode materials with both high rate and high capacity has become a top priority for developing high-performance hybrid capacitors.
[0003] Constructing a new porous structure is an important research direction for developing high-performance porous carbon. Among the numerous porous carbon materials, hierarchical porous carbon with 3D structure and porous carbon nanosheets with 2D structure have been widely used as capacitive electrode materials. Compared with 3D structure, carbon materials with 2D structure have shorter mass transfer distance and large lateral size, and are considered to have greater potential in the field of energy storage. Porous carbon materials with 2D structure are undoubtedly superior positive electrode materials for hybrid capacitors. The combination of nanometer thickness and rich pore structure can help reduce the tortuosity of the pores and accelerate the diffusion of electrolyte ions inside the pores. On the other hand, the sheet structure allows the electrolyte to directly contact the outer surface of the material, accelerating the external diffusion of electrolyte ions from the liquid phase to the solid surface of the electrode material, thereby greatly improving the utilization efficiency of the electrode material in the electrochemical reaction. As a typical two-dimensional nanomaterial, graphene has a large electrical conductivity and an ultra-high theoretical specific surface area (>2 630m 2 g -1 ), has been widely used as positive electrode materials for hybrid capacitors, but its high production cost and irreversible self-stacking still pose great challenges.
[0004] At present, the preparation of porous carbon nanosheets mainly includes the "top-down" method and the "bottom-up" method; the "top-down" method is to obtain nanosheets by exfoliating thicker 2D materials, including micromechanical exfoliation, mechanical force-assisted liquid exfoliation, ion insertion-assisted liquid exfoliation, ion exchange-assisted liquid exfoliation, oxidation-assisted liquid exfoliation, and selective etching-assisted liquid exfoliation. Its advantage is that it can produce carbon nanosheets with larger layers, but the thickness is relatively thick, and this method usually involves the use of toxic or strong oxidizing reagents, and the preparation process is relatively complicated. The "bottom-up" method is to form carbon nanosheets through the polymerization aromatization of small molecules, including chemical vapor deposition, wet chemical synthesis, and organic conversion. Although the preparation process is relatively simple, the product yield is relatively low and cannot be industrialized. Summary of the invention
[0005] In view of the problems in the prior art of complex preparation process, high cost and low yield of porous carbon nanosheets, the present invention provides a low-rank coal-based two-dimensional porous nanosheet, a preparation method and application.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention provides a method for preparing a low-rank coal-based two-dimensional porous nanosheet, comprising:
[0008] Purifying low-rank coal to obtain purified low-rank coal;
[0009] The purified low-rank coal, surfactant, alkali and water are mixed, reacted at 30°C to 90°C for 20 to 30 hours, and dried to obtain a layered intermediate; wherein the drying temperature is 70°C to 100°C;
[0010] The layered intermediate is subjected to high temperature carbonization treatment to obtain a porous carbon material;
[0011] The porous carbon material is acid-washed, water-washed and dried to obtain low-rank coal-based two-dimensional porous nanosheets.
[0012] Furthermore, the method for purifying low-rank coal to obtain purified low-rank coal is:
[0013] The low-rank coal is subjected to alkali dissolution treatment to obtain low-rank coal liquid;
[0014] The low-rank coal liquid is subjected to acid precipitation treatment, water washing and drying to obtain purified low-rank coal; wherein the drying temperature is 45°C to 60°C.
[0015] Furthermore, the conditions for alkali dissolution treatment of low-rank coal are:
[0016] The alkali solution used in the alkali dissolution treatment is a sodium hydroxide solution and / or a potassium hydroxide solution with a concentration of 1 to 12 mol / L;
[0017] The mass ratio of the low-rank coal to the alkali solution is 1:(3-15);
[0018] The alkali dissolution treatment time is 1 to 6 hours, and the temperature is 20° C. to 90° C.
[0019] Furthermore, the conditions for acid precipitation treatment of low-rank coal liquid are:
[0020] The acid solution used in the acid precipitation treatment is one or more of a hydrochloric acid solution, a nitric acid solution, a sulfuric acid solution and a hydrofluoric acid solution with a concentration of 1 to 12 mol / L;
[0021] The mass ratio of the low-grade coal liquid to the acid liquid is 1:(3-15);
[0022] The acid precipitation treatment time is 1 to 6 hours, and the temperature is 20° C. to 60° C.
[0023] Furthermore, the mass ratio of the purified low-rank coal, surfactant and alkali is 2:1:(8-12).
[0024] Furthermore, the temperature of the high-temperature carbonization treatment of the layered intermediate is 200° C. to 1000° C., the heating rate is 0.5 to 5° C. / min, and the time of the high-temperature carbonization treatment is 2 to 6 hours.
[0025] Furthermore, the porous carbon material is acid washed with a 0.1-2 mol / L hydrochloric acid solution.
[0026] Preferably, the low-rank coal is weathered coal or lignite.
[0027] A low-rank coal-based two-dimensional porous nanosheet is prepared using the method.
[0028] For example, the application of low-rank coal-based two-dimensional porous nanosheets in the preparation of positive electrodes for hybrid capacitors.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The present invention provides a method for preparing a low-rank coal-based two-dimensional porous nanosheet, which comprises the following steps: purifying low-rank coal to obtain purified low-rank coal; mixing the purified low-rank coal, a surfactant, an alkali and water, and drying to obtain a layered intermediate; subjecting the layered intermediate to a high-temperature carbonization treatment to obtain a porous carbon material; and subjecting the porous carbon material to acid washing, water washing and drying to obtain a low-rank coal-based two-dimensional porous nanosheet. This method uses low-rank coal as a carbon source. Compared with other coals, its structural characteristics of being rich in polycyclic aromatic hydrocarbons enable it to obtain larger carbon nanosheets with a higher carbon yield. The low-rank coal and a surfactant are evenly mixed under high-temperature reaction to form a stable layered liquid microcrystalline structure, which, after undergoing high-temperature carbonization, obtains an ultra-thin two-dimensional porous structure through two-dimensional self-assembly. This structure helps to reduce the tortuosity of the pores and accelerate the diffusion of electrolyte ions inside the pores. On the other hand, the sheet structure allows the electrolyte to directly contact the outer surface of the material, accelerating the external diffusion of electrolyte ions from the liquid phase to the solid phase surface of the electrode material, thereby greatly improving the utilization efficiency of the electrode material in the electrochemical reaction. The preparation process is simple, the production cost is low, and it is easy to mass produce.
[0031] The present invention provides a low-rank coal-based two-dimensional porous nanosheet, which is prepared by the above method. The low-rank coal-based two-dimensional porous nanosheet has a high yield and a two-dimensional porous sheet structure, which helps to reduce the tortuosity of the pores, accelerate the diffusion of electrolyte ions inside the pores, and enable the electrolyte to directly contact the outer surface of the material, accelerate the external diffusion of electrolyte ions from the liquid phase to the solid phase surface of the electrode material, thereby greatly improving the utilization efficiency of the electrode material in the electrochemical reaction.
[0032] For example, the application of low-order coal-based two-dimensional porous nanosheets in the preparation of hybrid capacitor positive electrodes can produce capacitors with higher charging and discharging speeds and energy density, better capacitance performance and cycle stability, low cost, and easy industrialization. It has broad application prospects in energy storage fields such as supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The present invention is a schematic flow chart of a method for preparing a low-rank coal-based two-dimensional porous nanosheet.
[0034] Figure 2 This is a SEM image of the low-rank coal-based two-dimensional porous nanosheet prepared in Example 1 of the present invention.
[0035] Figure 3 This is the XRD pattern of the low-rank coal-based two-dimensional porous nanosheets prepared in Examples 1-3 of the present invention.
[0036] Figure 4 This is a Raman graph of the low-rank coal-based two-dimensional porous nanosheets prepared in Examples 1-3 of the present invention.
[0037] Figure 5 This is a graph showing the N2 adsorption-desorption curves of the low-rank coal-based two-dimensional porous nanosheets prepared in Examples 1-3 of the present invention.
[0038] Figure 6 This is a rate performance diagram of the low-rank coal-based two-dimensional porous nanosheets prepared in Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0039] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0040] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0041] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0042] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0043] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0044] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0045] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0046] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0047] See also Figure 1 The present invention discloses a method for preparing a low-rank coal-based two-dimensional porous nanosheet, comprising:
[0048] S1: Purify the low-rank coal to obtain purified low-rank coal, specifically:
[0049] The low-rank coal is subjected to alkali dissolution treatment to obtain low-rank coal liquid: the low-rank coal is placed in a sodium hydroxide solution and / or potassium hydroxide solution with a concentration of 1 to 12 mol / L, at 20°C to 90°C, the alkali dissolution time is 1 to 6 hours, fully stirred, centrifuged, and the supernatant is taken as the low-rank coal liquid; wherein the mass ratio of the low-rank coal to the alkali liquid is 1:(3 to 15);
[0050] The low-rank coal liquid is subjected to acid precipitation treatment, water washing and drying to obtain purified low-rank coal: the low-rank coal liquid is mixed with one or more acid solutions selected from hydrochloric acid solution, nitric acid solution, sulfuric acid solution and hydrofluoric acid solution with a concentration of 1 to 12 mol / L, subjected to acid precipitation treatment at 20°C to 60°C for 1 to 6 hours, and then washed with water for multiple times until the solution is neutral, centrifuged, and dried at 45°C to 60°C to obtain purified low-rank coal; wherein the mass ratio of the low-rank coal liquid to the acid solution is 1:(3 to 15).
[0051] S2: Mix the purified low-rank coal, surfactant, alkali and water, and dry them to obtain a layered intermediate, specifically:
[0052] The purified low-rank coal, surfactant and alkali are mixed in water at a mass ratio of 2:1:(8-12) to form a mixed solution, reacted at 30°C-90°C for 20-30 hours, and dried at 70°C-100°C to obtain a layered intermediate, wherein the concentration of the alkali in the mixed solution is 0.7-1.1 mol / L.
[0053] S3: subjecting the layered intermediate to high-temperature carbonization treatment to obtain a porous carbon material, specifically:
[0054] In a high-purity nitrogen or argon protective atmosphere, the layered intermediate is heated to 200°C to 1000°C at a heating rate of 0.5 to 5°C / min for a high-temperature carbonization treatment for 2 to 6 hours to obtain a porous carbon material;
[0055] S4: acid-washing, water-washing and drying the porous carbon material to obtain a low-rank coal-based two-dimensional porous nanosheet, specifically:
[0056] The porous carbon material is pickled in a hydrochloric acid solution with a concentration of 0.1 to 2 mol / L, then washed with water for multiple times until neutral, and dried at 50° C. to obtain a low-rank coal-based two-dimensional porous nanosheet.
[0057] Preferably, the low-rank coal is weathered coal or lignite; the surfactant is an amphiphilic diblock copolymer or an amphiphilic triblock copolymer, preferably F127 or P123.
[0058] Example 1
[0059] The lignite is placed in a 6mol / L sodium hydroxide solution and subjected to an alkali dissolution treatment for 3 hours at 60°C; the mass ratio of the alkali-dissolved lignite to the sodium hydroxide solution is 1:10; the mixture is fully stirred and centrifuged to obtain a low-rank coal liquid; the low-rank coal liquid is placed in a 6mol / L hydrochloric acid solution and subjected to an acid precipitation treatment for 4 hours at 50°C; the mass ratio of the low-rank coal liquid to the hydrochloric acid solution is 1:10; after the acid precipitation treatment, the mixture is washed and centrifuged several times until the solution is close to neutral, and dried to obtain purified low-rank coal; the purified low-rank coal, F127 and potassium hydroxide are dissolved in deionized water at a mass ratio of 2:1:10 to form a mixed solution, stirred at 90°C for 24 hours, and dried at 70°C to obtain a layered intermediate; the concentration of the mixed solution is 0.7mol / L;
[0060] The layered intermediate was placed in a N2 atmosphere and heated to 800°C at a heating rate of 2°C / min for high-temperature carbonization treatment for 2 h to obtain a porous carbon material;
[0061] The porous carbon material was acid-washed in a hydrochloric acid solution with a concentration of 0.1 mol / L, then washed with water until neutral, and dried at 50° C. to obtain a low-rank coal-based two-dimensional porous nanosheet.
[0062] Example 2
[0063] The lignite is placed in a 6 mol / L sodium hydroxide solution and subjected to an alkali dissolution treatment for 3 hours at 60°C; the mass ratio of the alkali-dissolved lignite to the sodium hydroxide solution is 1:10; the mixture is centrifuged after sufficient stirring to obtain a low-rank coal liquid; the low-rank coal liquid is placed in a 6 mol / L hydrochloric acid solution and subjected to an acid precipitation treatment for 4 hours at 50°C; the mass ratio of the low-rank coal liquid to the hydrochloric acid solution is 1:10; after the acid precipitation treatment, the mixture is washed and centrifuged multiple times until the solution is close to neutral, and dried to obtain purified low-rank coal;
[0064] The purified low-rank coal, F127 and potassium hydroxide were dissolved in deionized water at a mass ratio of 2:1:8 to form a mixed solution, which was stirred at 90°C for 24 hours and dried at 70°C to obtain a layered intermediate; the concentration of the mixed solution was 0.7 mol / L;
[0065] The layered intermediate was placed in a N2 atmosphere and heated to 800°C at a heating rate of 2°C / min for high-temperature carbonization treatment for 2 h to obtain a porous carbon material;
[0066] The porous carbon material was acid-washed in a hydrochloric acid solution with a concentration of 0.1 mol / L, then washed with water until neutral, and dried at 50° C. to obtain a low-rank coal-based two-dimensional porous nanosheet.
[0067] Example 3
[0068] The lignite is placed in a 6mol / L sodium hydroxide solution and subjected to an alkali dissolution treatment for 3 hours at 60°C; the mass ratio of the alkali-dissolved lignite to the sodium hydroxide solution is 1:10; the mixture is fully stirred and centrifuged to obtain a low-rank coal liquid; the low-rank coal liquid is placed in a 6mol / L hydrochloric acid solution and subjected to an acid precipitation treatment for 4 hours at 50°C; the mass ratio of the low-rank coal liquid to the hydrochloric acid solution is 1:10; after the acid precipitation treatment, the mixture is washed and centrifuged several times until the solution is close to neutral, and dried to obtain purified low-rank coal; the purified low-rank coal, F127 and potassium hydroxide are dissolved in deionized water at a mass ratio of 2:1:12 to form a mixed solution, stirred at 90°C for 24 hours, and dried at 70°C to obtain a layered intermediate; the concentration of the mixed solution is 0.7mol / L;
[0069] The layered intermediate was placed in a N2 atmosphere and heated to 800°C at a heating rate of 2°C / min for high-temperature carbonization treatment for 2 h to obtain a porous carbon material;
[0070] The porous carbon material was acid-washed in a hydrochloric acid solution with a concentration of 0.1 mol / L, then washed with water until neutral, and dried at 50° C. to obtain a low-rank coal-based two-dimensional porous nanosheet.
[0071] See also Figures 2 to 5In order to test the performance of the low-rank coal-based two-dimensional porous nanosheets prepared by the present invention, the low-rank coal-based two-dimensional porous nanosheets prepared in Examples 1-3 were subjected to SEM, XRD, Raman and N2 adsorption and desorption tests in sequence. It can be seen that the low-rank coal-based two-dimensional porous nanosheets prepared by the present invention are sponge-like and have obvious open pores, which help to reduce the tortuosity of the pores and accelerate the diffusion of electrolyte ions in the pores. The electrolyte can directly contact the outer surface of the material, accelerate the external diffusion of electrolyte ions from the liquid phase to the solid phase surface of the electrode material, and thus greatly improve the utilization efficiency of the electrode material in the electrochemical reaction. D / I G The value is above 1.6, indicating that the prepared low-rank coal-based two-dimensional porous nanosheets have more defects, further indicating that the two-dimensional porous nanosheets have more active sites. The specific surface area in the N2 adsorption-desorption curve is greater than 1700m 2 g -1 , indicating that the low-rank coal-based two-dimensional porous nanosheets have a higher specific surface area. Electrode materials with high specific surface area usually have more complex pore structures and more pore channels, which help the ions in the electrolyte to be quickly transported inside the electrode material. The fine particle size and more surface defects may also improve the electronic conductivity of the electrode material, thereby improving the overall electrochemical performance.
[0072] See also Figure 6 In order to test the performance of the low-order coal-based two-dimensional porous nanosheets prepared in Examples 1-3 as positive electrode materials, the low-order coal-based two-dimensional porous nanosheets prepared in Examples 1-3 were mixed with conductive carbon black and polyvinylidene fluoride in a ratio of 8:1:1 to obtain positive electrode slurry; the positive electrode slurry was evenly coated on aluminum foil, and cut into electrode sheets with a diameter of 15 mm after vacuum drying; the electrode sheet was used as the working electrode, the sodium sheet was used as the counter electrode, the glass fiber was used as the diaphragm, and NaClO4 was used as the electrolyte, and the battery was assembled in a glove box filled with argon. The rate performance test was also carried out, and it was found that when the current density increased from 0.1 to 10Ag -1 (120.9 to 88 mAhg -1 ), the material achieved a high capacity retention rate of 73.3%. It should be noted that LCN4-LCN6 in the figure refer to the usage ratios of alkali to purified low-rank coal of 4:1, 5:1 and 6:1 respectively.
[0073] Example 4
[0074] The weathered coal is placed in a 1 mol / L potassium hydroxide solution and subjected to an alkali dissolution treatment for 6 hours at 90°C; the mass ratio of the weathered coal subjected to the alkali dissolution treatment to the potassium hydroxide solution is 1:15; the mixture is centrifuged after being fully stirred to obtain a low-rank coal liquid; the low-rank coal liquid is placed in a 1 mol / L hydrochloric acid solution and subjected to an acid precipitation treatment for 6 hours at 60°C; the mass ratio of the low-rank coal liquid to the hydrochloric acid solution is 1:15; after the acid precipitation treatment, the mixture is washed and centrifuged several times until the solution is close to neutral, and dried to obtain purified low-rank coal; the purified low-rank coal, F127 and potassium hydroxide are dissolved in deionized water at a mass ratio of 2:1:11 to form a mixed solution, stirred at 80°C for 26 hours, and dried at 80°C to obtain a layered intermediate; the concentration of the mixed solution is 0.8 mol / L;
[0075] The layered intermediate was placed in a N2 atmosphere and heated to 500°C at a heating rate of 2°C / min for high-temperature carbonization treatment for 4 hours to obtain a porous carbon material;
[0076] The porous carbon material was acid-washed in a hydrochloric acid solution with a concentration of 0.1 mol / L, then washed with water until neutral, and dried at 60° C. to obtain a low-rank coal-based two-dimensional porous nanosheet.
[0077] Example 5
[0078] The weathered coal is placed in a 2mol / L potassium hydroxide solution and subjected to an alkali dissolution treatment for 3 hours at 80°C; the mass ratio of the weathered coal subjected to the alkali dissolution treatment to the potassium hydroxide solution is 1:6; the mixture is centrifuged after being fully stirred to obtain a low-rank coal liquid; the low-rank coal liquid is placed in a 2mol / L hydrochloric acid solution and subjected to an acid precipitation treatment for 3 hours at 45°C; the mass ratio of the low-rank coal liquid to the hydrochloric acid solution is 1:6; after the acid precipitation treatment, the mixture is washed and centrifuged several times until the solution is close to neutral, and dried to obtain purified low-rank coal; the purified low-rank coal, F127 and potassium hydroxide are dissolved in deionized water at a mass ratio of 2:1:10 to form a mixed solution, which is stirred at 50°C for 30 hours and dried at 100°C to obtain a layered intermediate; the concentration of the mixed solution is 1mol / L;
[0079] The layered intermediate was placed in a N2 atmosphere and heated to 200°C at a heating rate of 0.5°C / min for high-temperature carbonization treatment for 6 hours to obtain a porous carbon material;
[0080] The porous carbon material was acid-washed in a hydrochloric acid solution with a concentration of 0.1 mol / L, then washed with water until neutral, and dried at 70° C. to obtain a low-rank coal-based two-dimensional porous nanosheet.
[0081] Example 6
[0082] The weathered coal is placed in a 12mol / L sodium hydroxide solution and subjected to an alkali dissolution treatment for 2h at 20°C; the mass ratio of the weathered coal subjected to the alkali dissolution treatment to the sodium hydroxide solution is 1:5; the mixture is centrifuged after being fully stirred to obtain a low-rank coal liquid; the low-rank coal liquid is placed in a 10mol / L hydrochloric acid solution and subjected to an acid precipitation treatment for 6h at 20°C; the mass ratio of the low-rank coal liquid to the hydrochloric acid solution is 1:8; after the acid precipitation treatment, the mixture is washed and centrifuged several times until the solution is close to neutral, and dried to obtain purified low-rank coal; the purified low-rank coal, F127 and potassium hydroxide are dissolved in deionized water at a mass ratio of 2:1:9 to form a mixed solution, stirred at 20°C for 30h, and dried at 100°C to obtain a layered intermediate; the concentration of the mixed solution is 1.1mol / L;
[0083] The layered intermediate was placed in a N2 atmosphere and heated to 1000°C at a heating rate of 5°C / min for high-temperature carbonization treatment for 2 hours to obtain a porous carbon material;
[0084] The porous carbon material was acid-washed in a hydrochloric acid solution with a concentration of 0.5 mol / L, then washed with water until neutral, and dried at 70° C. to obtain a low-rank coal-based two-dimensional porous nanosheet.
[0085] Example 7
[0086] The lignite is placed in a 10mol / L sodium hydroxide solution and subjected to an alkali dissolution treatment for 1 hour at 30°C; the mass ratio of the alkali-treated lignite to the sodium hydroxide solution is 1:7; the mixture is fully stirred and centrifuged to obtain a low-rank coal liquid; the low-rank coal liquid is placed in a 9mol / L hydrofluoric acid solution and subjected to an acid precipitation treatment for 2 hours at 40°C; the mass ratio of the low-rank coal liquid to the hydrofluoric acid solution is 1:7; after the acid precipitation treatment, the mixture is washed and centrifuged several times until the solution is close to neutral, and dried to obtain purified low-rank coal; the purified low-rank coal, F127 and potassium hydroxide are dissolved in deionized water at a mass ratio of 2:1:12 to form a mixed solution, stirred at 70°C for 29 hours, and dried at 80°C to obtain a layered intermediate; the concentration of the mixed solution is 0.9mol / L;
[0087] The layered intermediate was placed in a N2 atmosphere and heated to 700°C at a heating rate of 2°C / min for a high-temperature carbonization treatment for 4 hours to obtain a porous carbon material;
[0088] The porous carbon material was acid-washed in a hydrochloric acid solution with a concentration of 1 mol / L, then washed with water until neutral, and dried at 70° C. to obtain a low-rank coal-based two-dimensional porous nanosheet.
[0089] Example 8
[0090] The lignite is placed in a mixture of 10mol / L sodium hydroxide solution and 10mol / L potassium hydroxide solution, and alkali-dissolved for 5 hours at 45°C; the mass ratio of the alkali-dissolved lignite to the alkali solution is 1:7; the mixture is fully stirred and centrifuged to obtain a low-rank coal liquid; the low-rank coal liquid is placed in an 11mol / L hydrochloric acid solution and acid-precipitated for 1 hour at 55°C; the mass ratio of the low-rank coal liquid to the hydrochloric acid solution is 1:13; after the acid precipitation treatment, the mixture is washed and centrifuged several times until the solution is close to neutral, and dried to obtain purified low-rank coal; the purified low-rank coal, P123 and sodium hydroxide are dissolved in deionized water at a mass ratio of 2:1:10 to form a mixed solution, stirred at 75°C for 28 hours, and dried at 90°C to obtain a layered intermediate; the concentration of the mixed solution is 0.75mol / L;
[0091] The layered intermediate was placed in a N2 atmosphere and heated to 600°C at a heating rate of 3°C / min for high-temperature carbonization treatment for 4 hours to obtain a porous carbon material;
[0092] The porous carbon material was acid-washed in a hydrochloric acid solution with a concentration of 1.5 mol / L, then washed with water until neutral, and dried at 70° C. to obtain a low-rank coal-based two-dimensional porous nanosheet.
[0093] Example 9
[0094] The lignite is placed in a mixture of 9 mol / L potassium hydroxide solution, and alkali-dissolved for 3 hours at 45°C; the mass ratio of the alkali-dissolved lignite to the potassium hydroxide solution is 1:9; the mixture is fully stirred and centrifuged, and the supernatant is taken to obtain a low-rank coal liquid; the low-rank coal liquid is placed in a 9 mol / L sulfuric acid solution, and acid-precipitated for 1 hour at 55°C; the mass ratio of the low-rank coal liquid to the sulfuric acid solution is 1:13; after the acid precipitation treatment, the multiple washing and centrifugation are performed until the solution is close to neutral, and dried to obtain purified low-rank coal; the purified low-rank coal, F127 and sodium hydroxide are dissolved in deionized water at a mass ratio of 2:1:12 to form a mixed solution, stirred at 35°C for 30 hours, and dried at 70°C to obtain a layered intermediate; the concentration of the mixed solution is 1.05 mol / L;
[0095] The layered intermediate was placed in a N2 atmosphere and heated to 600°C at a heating rate of 1°C / min for high-temperature carbonization treatment for 4 hours to obtain a porous carbon material;
[0096] The porous carbon material was acid-washed in a hydrochloric acid solution with a concentration of 2 mol / L, then washed with water until neutral, and dried at 70° C. to obtain a low-rank coal-based two-dimensional porous nanosheet.
[0097] Example 10
[0098] A low-rank coal-based two-dimensional porous nanosheet is prepared by the method described in any one of Examples 1 to 9. The low-rank coal-based two-dimensional porous nanosheet has a high yield and a two-dimensional porous sheet structure, which helps to reduce the tortuosity of the pores, accelerate the diffusion of electrolyte ions inside the pores, and enable the electrolyte to directly contact the outer surface of the material, accelerate the external diffusion of electrolyte ions from the liquid phase to the solid phase surface of the electrode material, thereby greatly improving the utilization efficiency of the electrode material in the electrochemical reaction.
[0099] Embodiment 11
[0100] The application of low-order coal-based two-dimensional porous nanosheets in preparing the positive electrode of a hybrid capacitor as described in Example 10. The prepared capacitor has a higher charge and discharge rate and energy density, better capacitance performance and cycle stability, low cost and easy industrialization, and has broad application prospects in energy storage fields such as supercapacitors.
[0101] In summary, the present invention provides a low-rank coal-based two-dimensional porous nanosheet, a preparation method and an application. A new preparation method for preparing low-rank coal-based porous carbon two-dimensional carbon nanosheets "from the middle to the top" is proposed. This method is based on the special "graphene oxide-like" characteristics of low-rank coal, that is, it is rich in aromatic structures and has a large number of oxygen-containing functional groups. The method uses the structural induction effect of surfactants to prepare high-yield porous carbon nanosheets, and then supplemented by 2D structural design to increase the electronic conduction characteristics of porous carbon, thereby greatly improving the utilization efficiency of electrode materials in electrochemical reactions. In addition, the process is simple, the conditions are mild, and the controllability is strong, which is more conducive to industrial promotion and application. The obtained carbon nanosheets show excellent electrochemical properties in hybrid capacitors. This method is not only expected to obtain porous carbon nanosheet electrode materials for high-performance hybrid capacitors, but also helps to broaden the application field of low-rank coal.
[0102] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.
Claims
1. A method for preparing low-rank coal-based two-dimensional porous nanosheets, characterized in that: include: Purifying low-rank coal to obtain purified low-rank coal; Specifically, low-rank coal is subjected to alkali dissolution treatment to obtain low-rank coal liquid; The low-rank coal liquid is subjected to acid precipitation treatment, water washing and drying to obtain purified low-rank coal; The purified low-rank coal, surfactant, alkali and water are mixed, reacted at 30°C to 90°C for 20 to 30 hours, and dried to obtain a layered intermediate; the drying temperature is 70°C to 100°C; The layered intermediate is subjected to high temperature carbonization treatment to obtain a porous carbon material; The porous carbon material is acid-washed, water-washed and dried to obtain low-rank coal-based two-dimensional porous nanosheets.
2. The method for preparing low-rank coal-based two-dimensional porous nanosheets according to claim 1, characterized in that: The low-rank coal is purified and the drying temperature of the purified low-rank coal is 45°C to 60°C.
3. The method for preparing low-rank coal-based two-dimensional porous nanosheets according to claim 2, characterized in that: The conditions for alkali dissolution treatment of low-rank coal are: The alkali solution used in the alkali dissolution treatment is a sodium hydroxide solution and / or a potassium hydroxide solution with a concentration of 1 to 12 mol / L; The mass ratio of the low-rank coal to the alkali solution is 1:(3-15); The alkali dissolution treatment time is 1 to 6 hours, and the temperature is 20° C. to 90° C.
4. The method for preparing low-rank coal-based two-dimensional porous nanosheets according to claim 2, characterized in that: The conditions for acid precipitation of low-rank coal liquid are: The acid solution used in the acid precipitation treatment is one or more of a hydrochloric acid solution, a nitric acid solution, a sulfuric acid solution and a hydrofluoric acid solution with a concentration of 1 to 12 mol / L; The mass ratio of the low-grade coal liquid to the acid liquid is 1:(3-15); The acid precipitation treatment time is 1 to 6 hours, and the temperature is 20° C. to 60° C.
5. The method for preparing low-rank coal-based two-dimensional porous nanosheets according to claim 1, characterized in that: The mass ratio of the purified low-rank coal, surfactant and alkali is 2:1:(8-12).
6. The method for preparing low-rank coal-based two-dimensional porous nanosheets according to claim 1, characterized in that: The temperature for high-temperature carbonization treatment of the layered intermediate is 200° C. to 1000° C., the heating rate is 0.5 to 5° C. / min, and the time for high-temperature carbonization treatment is 2 to 6 hours.
7. The method for preparing low-rank coal-based two-dimensional porous nanosheets according to claim 1, characterized in that: The porous carbon material is acid washed using a 0.1-2 mol / L hydrochloric acid solution.
8. The method for preparing low-rank coal-based two-dimensional porous nanosheets according to claim 1, characterized in that: The low-rank coal is weathered coal or lignite.
9. A low-rank coal-based two-dimensional porous nanosheet, characterized in that: Prepared by the method according to any one of claims 1 to 8.
10. Use of the low-rank coal-based two-dimensional porous nanosheet as claimed in claim 9 in preparing a positive electrode of a hybrid capacitor.
Citation Information
Patent Citations
Salvia splendens petal-based porous graphene-like carbon nanosheets as well as preparation method and application thereof
CN108751164A
Preparation method of low-rank coal-based porous carbon and application of low-rank coal-based porous carbon in supercapacitor
CN111710530A